Evaluating Creativity: How Idea Context and Rater Personality Affect Considerations of Novelty and Usefulness. Issue 4 (2nd October 2022) - Lloyd-Cox, James; Pickering, Alan; Bhattacharya, Joydeep
ABSTRACT: According to the standard definition, creative ideas must be both novel and useful. While a handful of recent studies suggest that novelty is more important than usefulness to evaluations of creativity, little is known about the contextual and interpersonal factors that affect how people weigh these two components when making an overall creativity judgment. We used individual participant regressions and mixed-effects modeling to examine how the contributions of novelty and usefulness to ratings of creativity vary according to the context of the idea (i.e., how relevant it is to the real world) and the personality of the rater. Participants ( N = 121) rated the novelty, usefulness, and creativity of ideas from two contexts: responses to the alternative uses task (AUT) and genuine suggestions for urban planning projects. We also assessed three personality traits of participants: openness, intellect, and risk-taking. We found that novelty contributed more to evaluations of creativity among AUT ideas than projects, while usefulness contributed more among projects than AUT ideas. Further, participants with higher openness and higher intellect placed a greater emphasis on novelty when evaluating AUT ideas, but a greater emphasis on usefulness when evaluating projects. No significant effects were found for the risk-taking trait. Plain Language Summary: Understanding how creativity is perceived and defined in different contexts and across different individuals is highly important, not just to our understanding of how to assess creativity, but to our understanding of creativity itself. However, relatively few existing studies have examined differences in how individuals evaluate creativity, and the factors they consider during their evaluations. We investigated how personality and problem context affect how individuals consider novelty and usefulness when making an overall creativity judgment. Participants rated ideas from two contexts: responses to a common lab-based measure of creative ability and genuine suggestions for urban planning projects (ideas with more real-world relevance). We also assessed three personality traits of participants: openness, intellect, and risk-taking. Data was analyzed using both individual participant regressions and linear mixed-effects models. We found that participants considered novelty more when evaluating the creativity of AUT ideas (relative to projects), and usefulness more when evaluating the creativity of projects (relative to AUT ideas). Furthermore, when evaluating the creativity of AUT ideas, participants with higher openness and higher intellect placed a greater emphasis on novelty, but when evaluating projects, these same participants placed a greater emphasis on usefulness. Overall, our findings highlight the importance of considering contextual and interpersonal factors when researchers examine how creativity is evaluated, defined, and perceived, strengthening recent calls for creativity assessments that can account for variation across raters.